Nipple reconstruction using a two-step purse-string suture technique - Van Laeken, Nancy (Pulsus Group Inc, 2011)
Formation of an aesthetic nipple areola complex with lasting projection remains a challenging final step in breast reconstruction. Despite the many techniques that have been described, no single approach has emerged as the gold standard. The current study presents a novel technique in nipple areola complex reconstruction. In a two-step fashion, the nipple and areola are reconstructed independently. This aims to create a lasting projection of the nipple while maintaining a natural contour among the nipple, the areola complex and the surrounding breast tissue. With more than 15 years of experience using this technique, the authors believe that it is a straightforward procedure and is reliable in providing satisfactory results to both the surgeon and the patient.